2018
DOI: 10.4149/neo_2018_170705n462
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA homeobox (HOX) A11-AS promotes malignant progression of glioma by targeting miR-124-3p

Abstract: Glioma is the most common and serious form of primary tumor in adult central nervous system. HOXA11-AS is a LncRNA located in the HOXA gene cluster. In the present study, we investigated the expression and function of LncRNA HOXA11-AS in glioma tissues and cells. We found that LncRNA HOXA11-AS expression was markedly elevated in glioma tissues compared to normal brain tissues. The LncRNA HOXA11-AS expression in cases of high-grade glioma was significantly higher than that in cases of low-grade. Patients with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…27 The silence of HOXA11-AS was also showed to reduce proliferation and metastasis but expedite apoptosis of glioma cells. 28 Lu et al unraveled that HOXA11-AS knockdown reduced proliferation and invasion abilities, but induced apoptosis of uveal melanoma (UM) cells. 29 But the role of HOXA11-AS in cutaneous melanoma is almost unclear.…”
Section: Discussionmentioning
confidence: 99%
“…27 The silence of HOXA11-AS was also showed to reduce proliferation and metastasis but expedite apoptosis of glioma cells. 28 Lu et al unraveled that HOXA11-AS knockdown reduced proliferation and invasion abilities, but induced apoptosis of uveal melanoma (UM) cells. 29 But the role of HOXA11-AS in cutaneous melanoma is almost unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, on this basis, another study of the group reported that HOXA11-AS is highly expressed in non-small cell lung cancer tissues and cell lines. The proliferation, migration, invasion, and invasion of non-small cell lung cancer cells after HOXAl1-AS knockout Both tumorigenicity and angiogenesis are inhibited, while apoptosis is increased, and the cell cycle is arrested in GO/G1 or G2/M phase [21]. Further research found that HOXA11-AS may exert its above biological functions in non-small cell lung cancer by regulating the expression of miR-642b-3p and PDE4D [22].…”
Section: Non-small Cell Lung Cancermentioning
confidence: 92%
“…Overall, almost all oncogene lncRNAs regulate the cell cycle, promote tumor proliferation, inhibit apoptosis, and induce tumor invasiveness and migration. While lncRNAs such as XIST (162-172), CRDNE (173-179), FOXD2-AS1 (186)(187)(188)(189)(190)(191)(192)(193)(194), ANRIL (195)(196)(197), HOXA11-AS (198)(199)(200)(201)(202)(203), TP73-AS1 (204)(205)(206), and DANCR (207-210) are only known as tumor inducers, the ultimate function of some lncRNAs is controversial. For instance, for MALAT1, NEAT1, and TUG1, both oncogenic and tumor suppressor effects have been reported.…”
Section: Role In Tumor Pathologymentioning
confidence: 99%